Segmentation and tagmosis in Chelicerata. Issue 3 (May 2017) - Dunlop, Jason A.; Lamsdell, James C.
Abstract: Patterns of segmentation and tagmosis are reviewed for Chelicerata. Depending on the outgroup, chelicerate origins are either among taxa with an anterior tagma of six somites, or taxa in which the appendages of somite I became increasingly raptorial. All Chelicerata have appendage I as a chelate or clasp-knife chelicera. The basic trend has obviously been to consolidate food-gathering and walking limbs as a prosoma and respiratory appendages on the opisthosoma. However, the boundary of the prosoma is debatable in that some taxa have functionally incorporated somite VII and/or its appendages into the prosoma. Euchelicerata can be defined on having plate-like opisthosomal appendages, further modified within Arachnida. Total somite counts for Chelicerata range from a maximum of nineteen in groups like Scorpiones and the extinct Eurypterida down to seven in modern Pycnogonida. Mites may also show reduced somite counts, but reconstructing segmentation in these animals remains challenging. Several innovations relating to tagmosis or the appendages borne on particular somites are summarised here as putative apomorphies of individual higher taxa. We also present our observations within the concept of pseudotagma, whereby the true tagmata – the prosoma and opisthosoma – can be defined on a fundamental change in the limb series while pseudotagmata, such as the cephalosoma/proterosoma, are expressed as divisions in sclerites covering the body without an accompanying change in the appendages. Highlights: Patterns of segmentation are reviewed across extinct and living representatives of the Chelicerata (arachnids and their relatives). The main trend has been the consolidation of limbs for food gathering and locomotion in the front half of the body as the prosoma, and for respiration in the back half of the body as the opisthosoma. The transitional region between the prosoma and opisthosoma is especially complex, with several taxa showing reductions or modifications of the segment or its limbs here. Key evolutionary innovations within the Chelicerata relating to segments or the appendages borne on these segments are highlighted.